Syrian refugees in Turkey: Changing attitudes and fortunes - Suat Kınıklıoğlu (Stiftung Wissenschaft und Politik (SWP), 2020)
In view of a substantial loss in local elections and an urge to demonstrate that the Turkish government is in control of the situation, Ankara's attitude toward the approximately four million Syrian refugees changed in July 2019. Security forces started to round up Syrian refugees, send them back to the Turkish provinces where they were registered, deport some, and encourage others to move to areas controlled by Turkey in northern Syria, including the conflict zone Idlib. The change in Turkish policy vis-à-vis the Syrian refugees as well as dramatic developments in Idlib have renewed international attention to the plight of the refugees. Ankara needs continued European support to deal with the situation, particularly if a new wave of refugees is forced to flee to Turkey from Idlib.
Keywords: 320